Experimental comparative study of the use of chatGPT and its influence on the learning of students of the Information Technologies career at the University of Guayaquil - Diaz Vera, Janeth Pilar; Peña Hojas, Delia Silvia; Fabara Sarmiento, Zoila Jessenia; Ruiz Ramírez, Alicia Karina; Macías Mora, Diana Verónica (Revista Universidad de Guayaquil, 2023)
This article analyzes the impact of the use of ChatGPT and its influence on the learning of 48 students of the Information Technologies career at the University of Guayaquil. As a methodology, an experimental comparative study was carried out, for which the study population was divided into two groups of 24 students, one that used ChatGPT and the other that did not. In addition, a survey was conducted to assess student satisfaction with the use of ChatGPT and the perception of its impact on learning and teaching. A descriptive statistical analysis was carried out to compare the academic performance of the experimental group and the control group, with these data the analysis of variance (ANOVA) was made to evaluate the difference in grades between the two groups. The results suggest the use of ChatGPT can be an effective teaching strategy to improve the academic performance of students, according to the results. However, more studies with larger samples are needed to evaluate the long-term impact of this tool in higher education, but the result of this research projects that this tool can have a significant and positive impact in higher education.
Keywords: ChatGPT; Educational quality; University learning; Artificial intelligence